Relationship between markers of inflammation and hemodynamic stress and death in patients with out-of-hospital cardiac arrest - Thomas A. Zelniker (Nature Portfolio, 2021)
Abstract Biomarkers that reflect hemodynamic stress, inflammation, extracellular matrix remodeling, angiogenesis, and endothelial dysfunction may improve risk stratification and add valuable pathobiological insight in patients with out-of-hospital cardiac arrest (OHCA). In total, 120 patients with OHCA who survived at least 48 h after return of spontaneous circulation were consecutively included in the present analysis. Concentrations of 30 biomarkers were measured simultaneously using a multi-panel biomarker assay. Cox regression models were adjusted for age, sex, estimated glomerular filtration rate, lactate concentration, bystander resuscitation, initial cardiac rhythm, and type of targeted temperature management. Overall, 57 patients (47.5%) had a favorable neurological outcome (Cerebral Performance Category ≤ 2) at 30 days, while palliative care was initiated in 49 patients (40.8%), and 52 patients (43.3%) died. After correction for multiple testing with Bonferroni-Holm, 8 biomarkers (including Angiopoietin-2, Procalcitonin, Resistin, IL-4Rα, MMP-8, TNFα, Renin, and IL-1α) were significantly associated with all-cause death. After multivariable adjustment, only angiopoietin-2 (Adjusted (Adj) hazard ratio (HR) per 1-unit increase in standardized biomarker concentrations 1.52 (95% CI 1.16–1.99)) and renin (Adj HR 1.32 (95% CI 1.06–1.65) remained independently associated with an increased risk of death. The discriminatory performance indicated good performance for angiopoietin-2 (area under the curve (AUC): 0.75 (95% CI 0.66–0.75) and was significantly higher (P = 0.011) as compared with renin (AUC: 0.60, 95% CI 0.50–0.60). In conclusion, angiopoietin-2 was significantly associated with all-cause mortality in patients with OHCA who survived the first 48 h and may prove to be useful for risk stratification of these patients.